Implementation Of Corporate Social Responsibility (CSR) Policy in Bogor City - Novida Waskitaningsih; Lilis Sri Mulyawati; Janthy Trilusianthy Hidayat (Riviera Publishing, 2025)
Corporate Social Responsibility (CSR) is a source of non-conventional financing that can be used as an alternative for local governments in providing infrastructure and development due to not maximizing regional income. The Bogor City Government realizes the importance of using CSR as a source of non-conventional financing by enacting Regional Regulation no. 6 of 2016 and Bogor Mayor Regulation No. 69 of 2017. This regulation is expected to become the legal basis for the Bogor City Government to establish a mechanism for implementing corporate CSR in an integrated and sustainable manner. Thus, the Bogor City Government can direct the company's CSR programs so that they are aligned with the Bogor City development priority programs. This study aims to determine the implementation of CSR policies in Bogor City. Data collection was carried out through document review and in-depth interviews to then be analyzed using descriptive qualitative analysis techniques. The results of the study show that CSR regulations in Bogor City have not been fully implemented, especially those related to CSR financing, implementation mechanisms, monitoring and control, as well as awarding and administrative sanctions. The regulation, which should have been implemented gradually since 2016, has not yet been socialized optimally to all companies in Bogor City, one of which is due to the COVID-19 pandemic. When associated with the theory of policy implementation, Bogor City already has an organization according to CSR policies, with the establishment of a facilitation team and secretariat, as well as a CSR forum. However, there is not yet a common interpretation of CSR policies, especially among companies, so that the impact on the not yet optimal application of Bogor City's CSR policies. The incompatibility of the implementation of this CSR policy ultimately has an effect on the not maximal contribution of CSR to the development of Bogor City.